Evaluation of the Super Tax Deduction Policy on Research and Development Activities in Indonesia - KRISTANTI, Kalyana Mitta; SAPTONO, Prianto Budi (PT Keberlanjutan Strategis Indonesia, 2023)
The Indonesian government encourages industrial sector participation in research and development (R&D) activities. One of the government's supports in increasing private R&D is issuing a super tax deduction (STD) policy for R&D activities. However, the number of taxpayers who have received confirmation of conformity to carry out R & D still needs to be more extensive compared to the total number of taxpayers. This research aims to evaluate the effectiveness of applying STD to R&D activities. This study uses a qualitative method. Data collection was carried out through in-depth interviews and literature studies. The research results show that STD incentives are not fully effective with two-dimensional indicators. First, the suitable policy has not run optimally because the goal of providing STD incentives to increase research and development activities in Indonesia has not been achieved. Second, the right environmental dimension has yet to be effective due to the potential for multiple interpretations related to recognizing and recording R&D costs between accounting and taxes.